ANALISIS FAKTOR PENGHAMBAT PENYELESAIAN SKRIPSI MAHASISWA STIA BANTEN - Ade Hadiono Ade Hadiono (LPPM STIA Banten, 2017)
This research aims to determine the factors and factors that most dominantly influence the delay in completing STIA Banten Student Thesis. This type of research is survey research. The subjects in this research were students in semesters 8 to 10. Meanwhile, the objects of this research were the factors that influenced students' completion of their thesis. The population in this study was 48 students, the data collection methods used were questionnaires and documentation. The data were analyzed using factor analysis with the SPSS 17 program. The results of the study showed that the factors that influenced the delay in completing the STIA Banten Student Thesis were these factors were as follows: Internal Factors: (a)